‘Slag_Fun’ – A New Tool for Archaeometallurgy: Development of an Analytical (P)ED-XRF Method for Iron-Rich Materials - Harald Veldhuijzen (Papers from the Institute of Archaeology, 2003)
This paper describes the development of a new analytical tool for bulk chemical analysis of iron-rich archaeometallurgical remains by Polarising Energy Dispersive X-ray Fluorescence ((P)ED-XRF). Prompted by the ongoing archaeological and archaeometric analyses of early first millennium BC iron smelting and smithing finds from Tell Hammeh (az-Zarqa), Jordan, the creation of this tool has already benefited several studies on iron-rich slag, of widely varying provenance as well as age (Anguilano 2002; Chirikure 2002; Ige and Rehren 2003; Stanway 2003). Following an explanation of the archaeological background and importance of the Hammeh finds, the paper describes the technical foundations of XRF analysis and the design, development and application of the "slag_fun" calibration method.
Keywords: x-ray fluorescence; metallurgy; Jordan